2016
DOI: 10.4102/jir.v1i1.8
|View full text |Cite
|
Sign up to set email alerts
|

It is the glycaemic response to, not the carbohydrate content of food that matters in diabetes and obesity: The glycaemic index revisited

Abstract: IntroductionThere is currently substantial debate about the merits of an imminent United Kingdom (UK) tax on sugar-sweetened beverages and snacks that are high in sugar. 1 The most recent Scientific Advisory Committee report 2 advises a reduction of dietary sugar consumption in the UK; however, because of the furore surrounding sugar, the role of starchy carbohydrates as a source of blood sugar (glucose) has become understated, and the important role of the glycaemic index (GI) has become somewhat eclipsed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Meta-analysis has shown a sufficient reduction in dietary GI or GL does result in a dose-dependent reduction in body weight in free-living persons with diabetes without them attempting to control their food intake [37]. Reduced glycemic load by avoidance of high GI carbohydrate foods has also resulted in the loss of body weight and gaining control of T2D [85,86,87]. Lower GI diets have also helped body weight reduction and maintenance, particularly with a background diet high in protein [88,89,90].…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis has shown a sufficient reduction in dietary GI or GL does result in a dose-dependent reduction in body weight in free-living persons with diabetes without them attempting to control their food intake [37]. Reduced glycemic load by avoidance of high GI carbohydrate foods has also resulted in the loss of body weight and gaining control of T2D [85,86,87]. Lower GI diets have also helped body weight reduction and maintenance, particularly with a background diet high in protein [88,89,90].…”
Section: Resultsmentioning
confidence: 99%
“…In comparing the relative strengths of the T2D–GI and GL relations, it should be recognized, however, that it is not a question of which is better. GI and GL may find preference according to the situation of the person or patient [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis has revealed that lower GL diets, achieved using lower GI carbohydrate foods, result in a dose-dependent reduction in body weight among persons with varied glycemic control from normal to the diabetic state 59 . Further, avoidance of high GI foods to achieve a lower GL diet has proved effective in improving body weight and glycemic and lipidemic parameters over a mean of 13 months in prediabetic and diabetic patients 69, 70. Beneficial effects of low GI and GL have become evident in long-term primary prevention of obesity-associated diseases 75 .…”
Section: Discussionmentioning
confidence: 99%